The Representation of the Feminine (Mythocriticism) in the Episodes of the del Caballero Atrevido and the Islas dotadas from the Libro del Caballero Zifar - Álvarez García, Casandra Deyanira (Revista Melibea, 2024)
The fantasy chapters (mirabilia) of the Libro del Caballero Zifar that we propose to analyze (the adventure of the Caballero Atrevido and the journey of Roboán to the Islas dotadas), have in common that both knights are subject to a process of trials imposed by a beautiful, rich and powerful maiden. In addition, the devil appears to both of them transfigured into a beautiful woman; and finally, the knights are expelled from those worlds, which are accessed through water (another feminine element). Also, each chapter aims to show as an exemplum about the sins of avarice and betrayal. For this study, the concept of mytheme proposed by Gilbert Durand in The Anthropological Structures of the Imaginary (1981) will be used in order to identify the mythemes associated with the nocturnal regime, which includes, among other elements, the feminine, the intimate, the mother, the earth, such as: the cave, the cups, the boat, the castles, etc. As a proposal, we can say that the indoctrination of sins would be associated with mythemes of the nocturnal regime that keep the knight inside and in contact with mother earth. In this way, it will be possible to understand how the teaching of these sins is mainly constituted by mythemes of the nocturnal regime related to the medieval female representation.